Modeling Dynamic Background based on Linear Equation - Rahma, Abdul Monem S.; Abd, Nabaa Basil (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
Detection moving car in front view is difficult operation because of the dynamic background due to the movement of moving car and the complex environment that surround the car, to solve that, this paper proposed new method based on linear equation to determine the region of interest by building more effective background model to deal with dynamic background scenes. This method exploited the permitted region between cars according to traffic law to determine the region (road) that in front the moving car which the moving cars move on. The experimental results show that the proposed method can define the region that represents the lane in front of moving car successfully with precision over 94%and detection rate 86% and FoM 90%.